2012
DOI: 10.1055/s-0031-1300971
|View full text |Cite
|
Sign up to set email alerts
|

Low HCMV DNA Copies Can Establish Infection and Result in Significant Symptoms in Extremely Preterm Infants: A Prospective Study

Abstract: Breast milk (BM) is the main source of human cytomegalovirus (HCMV) infection. We examined whether the number of HCMV DNA copies in BM is related to HCMV infection in very low birth weight (VLBW) infants. We identified 11 pairs of VLBW infants and mothers. BM samples were collected every week until 10 weeks postpartum. Urine samples were collected from the infants within 1 week, at 6 to 8 weeks, at discharge, and whenever HCMV infection was suspected. HCMV DNA in BM was positive in 7 of 11 mothers and reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…Between 4 and 6 weeks postpartum, HCMV can be isolated from breast milk in up to 100% of HCMV IgG-positive mothers [1,2]. Very immature preterm infants are at the greatest risk of developing symptomatic HCMV infection via breast milk [3,4,5,6]. Previous reports on HCMV infection in preterm infants via breast milk have suggested that infected infants did not have any long-term sequelae [7,8] but new data from 2012 and 2013 showed a negative influence of HCMV infection on cognitive development [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Between 4 and 6 weeks postpartum, HCMV can be isolated from breast milk in up to 100% of HCMV IgG-positive mothers [1,2]. Very immature preterm infants are at the greatest risk of developing symptomatic HCMV infection via breast milk [3,4,5,6]. Previous reports on HCMV infection in preterm infants via breast milk have suggested that infected infants did not have any long-term sequelae [7,8] but new data from 2012 and 2013 showed a negative influence of HCMV infection on cognitive development [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While in Gambia HCMV excretion in colostrum and genital tract were observed in 100% of congenitally infected, and 48% of early infected infants 10 , a study from Japan showed, that in seven cases of very low birthweight (VLBW) infants the initial viral load in breastmilk in the first week p.p. ranges between 10 and <1000 copies/mL HCMV DNA 11 . In contrast, an Italian group detected viral DNA in 31 out of 57 (54%) colostrum samples 12 .…”
Section: Hcmv Reactivation During Lactationmentioning
confidence: 99%
“…However, other observations seem to be important in the context of prevention 11 . An inverse correlation between milk HCMV-specific IgG avidity and HCMV load was also found 20 .…”
Section: Hcmv Reactivation During Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission to breastfed infants occurs from 6% (depending on pretreatment like heating or cryopreservation) to 59% (native milk), and symptomatic CMV infection may occur in up to 4% 7. Whereas term newborns usually do not show clinical signs of infection,8 preterm infants are more likely to show clinical signs of CMV infection, from mild thrombopenia or leukocytopenia, icterus to severe sepsis-like symptoms 5 9–18. Therefore, different ways of CMV inactivation in breast milk have been tested, from freezing19–24 to short-term pasteurisation,21 25 microwave heating24 as well as ultraviolet C irradiation 26.…”
Section: Introductionmentioning
confidence: 99%